IMPROVING STUDENTâS SPEAKING SKILL TROUGHT ANIMATION MOVIE AT SIXTH GRADE SDN 002 UJUNGBATU KABUPATEN ROKAN HULU PROVINSI RIAU - -, Rosdalina; Rahayu, Pipit; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This study aimed to solve the problems that were found in preliminary study. The research problem that was formulated âHow can movie as media improve the speaking skill?â This research was conducted in SDN 002 UJUNGBATU, and the numbers of students were fiffteen. This research focussed on improving studentsâ speaking achievement by using movie as media. This study used Classroom Action Research (CAR) as the research method. The subject of this study was the sixth grade students of SDN 002 Ujungbatu that consist of fifteen students. The steps of research procedure, they were: preliminary study (planning, implementing, observing, and reflecting) and data analysis. The data analysis used quantitative data that was obtained from the test. The researcher used scoring rubric to measure the studentsâ score, and then calculate the mean score.